Tratamientos térmicos como alternativas para el control de podredumbres en postcosecha de mandarinas sin agroquímicos - Cocco, Mariángeles (2022)
Heat treatments such as curing in a chamber (T 37°C and HR 90%) and treatment by Immersion of mandarins in hot water are alternatives to avoid the use of agrochemicals1,2,3. However, it must be avoided that they alter other aspects of the quality of the fruits. (internal quality or dehydration). The objective was to evaluate water treatments at high temperature and cured for less than 24 hours, that are effective, without altering the quality of the fruits.